2016
DOI: 10.1371/journal.pone.0165235
|View full text |Cite
|
Sign up to set email alerts
|

ASIC1a Deficient Mice Show Unaltered Neurodegeneration in the Subacute MPTP Model of Parkinson Disease

Abstract: Inflammation contributes to the death of dopaminergic neurons in Parkinson disease and can be accompanied by acidification of extracellular pH, which may activate acid-sensing ion channels (ASIC). Accordingly, amiloride, a non-selective inhibitor of ASIC, was protective in an acute 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of Parkinson disease. To complement these findings we determined MPTP toxicity in mice deficient for ASIC1a, the most common ASIC isoform in neurons. MPTP was applied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Tyrosine hydroxylase‐positive (dopaminergic) cells in the lateral SNc of the right hemisphere (see supplemental Figure S1a and S1c) were stereologically counted using the optical fractionator method (StereoInvestigator v11; MicroBrightField, Williston, VT, USA) as described (Komnig et al . ,b). In brief, neurons were manually identified in 50 × 50 μm counting frames presented by the software using an Axio Imager 2 microscope (Carl Zeiss Vision, Göttingen, Germany) and an oil immersion 63x objective (NA 1.4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyrosine hydroxylase‐positive (dopaminergic) cells in the lateral SNc of the right hemisphere (see supplemental Figure S1a and S1c) were stereologically counted using the optical fractionator method (StereoInvestigator v11; MicroBrightField, Williston, VT, USA) as described (Komnig et al . ,b). In brief, neurons were manually identified in 50 × 50 μm counting frames presented by the software using an Axio Imager 2 microscope (Carl Zeiss Vision, Göttingen, Germany) and an oil immersion 63x objective (NA 1.4).…”
Section: Methodsmentioning
confidence: 99%
“…The density of TH‐positive striatal fibres was analysed as previously described (Komnig et al . ,b). In brief, fluorescence 8‐bit images were acquired as z‐stack with five slices 1 μm apart using an 60x oil objective (NA 1.35) and an IX81S1F microscope (Olympus, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Four types of ASICs include ASIC1 (ASIC1a and ASIC1b), ASIC2 (ASIC2a and ASIC2b), ASIC3, and ASIC4; ASIC1a, ASIC2a, and ASIC2b are located in the CNS, cerebral cortex, hippocampus, olfactory bulbs, cerebellum, and amygdala, whereas ASIC3 and ASIC4 are located in the peripheral nervous system. 42 There is evidence suggesting a role for ASICs in the progression of various diseases such as Alzheimer's disease, 43 Parkinson's disease, 44 ischemic stroke, 45,46 migraine, 47 epilepsy, 48 and pain. 49 Studies of Bhowmick et al showed that ASIC1a present in the brain mediates cell death through acidotoxicity in rat hippocampal slices deprived of oxygen.…”
Section: Acid-sensing Ion Channels and Inflammasomesmentioning
confidence: 99%
“…It is well known that 1‐methyl‐4‐pheny1‐1,2,3,6‐tetrahydropyridine (MPTP) causes typical PD symptoms in population . The animal experiments and clinical studies show that MPTP is resolved into positive ion MPP + (1‐methyl‐4‐pheny1) after going through the blood‐brain barrier (BBB), and the toxicity is marked by inhibiting the activity of respiratory chain complex phosphoesterase (NADH‐COQ).…”
Section: Pathogenesis Of Pdmentioning
confidence: 99%